A novel functional disperse dye doped with graphene oxide for improving antistatic properties of polyester fabric using one-bath dyeing method. Issue 5 (March 2020) - Fan, Lihua; Tan, Yongsong; Amesimeku, Jeremiah; Yin, Yunjie; Wang, Chaoxia
A novel functional disperse dye doped with graphene oxide for antistatic properties of polyester fabric was achieved, which means that the dyeing and antistatic finishing can be simultaneously obtained by a one-bath method. Functional dyes were used to dye polyester fabric by a high-temperature, high-pressure dyeing method. The surface microscopic morphology of the dyed polyester fabric, and the dispersion properties of the disperse dye, graphene oxide, and the functional disperse dye, were characterized by scanning electron microscopy. The effects of the dyeing temperature on the particle sizes of three dyeing liquors were explored; this revealed that the temperature of the dyeing process had no effect on particle size. The dosage and reduction time of graphene oxide were investigated. The surface electrical resistance of the dyed fabric, 9.8 × 10 6 Ω, obtained at a condition of 2% (o.m.f) graphene oxide with a reduction time of 30 min, achieved A-grade antistatic standard. Furthermore, the rubbing and washing fastness of the treated fabric were 4- and 4 ∼ 5 grades, respectively. This preparation of the functional disperse dye provides a possibility in one-bath dyeing and antistatic finishing of polyester fabric.